What Is a God? : Studies in the Nature of Greek Divinity. - Lloyd, Alan B. (Classical Press of Wales, The, 2009)
"In recent study Greek religion has often dissolved itself into many religions. The eleven original essays here focus both on extremes of the Greek world and on its classical 'centre'. Distinguished scholars examine the earliest traces of religious thought in the Minoan and Mycenaean cultures. Striking similarities are revealed between religious ideas of Greece and of non-Greek Asia. There are special studies of Apollo, Athena, and Dionysiac religion. And new patterns are identified in the archaic and classical thought of Heraclitus, Herodotus and Sophocles"--Back cover.